2015
DOI: 10.1002/jmor.20411
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated allometric structures in relation to demographic and ecological parameters inLucanus cervus(Coleoptera: Lucanidae)

Abstract: Enlarged weapons and ornamental traits under sexual selection often show a positive allometric relationship with the overall body size. The present study explores the allometry of mandibles and their supporting structure, the head, in males of the European stag beetle, Lucanus cervus. This species shows a remarkable dimorphism in mandible shape and size that are used by males in intraspecific combats. Stag beetles were captured, measured, weighed, and released in the framework of a capture-mark-recapture study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…Using a traditional morphometric approach, Romiti et al (2015) highlighted the presence of two morphological classes: large males (which invest significantly more in mandibles and head size) and minor males. Furthermore, a geometric morphometric approach revealed that smaller males show highly variable mandibles (usually less curve dorsoventrally, thickset, with barely outlined teeth and a head without prominent basal edges) whereas larger males exhibit less variable mandibles (slender and equipped with fully developed median teeth, and deep, divaricate apical forks, supported by wide head basal edges) (Romiti et al 2016).…”
Section: Morphologymentioning
confidence: 99%
“…Using a traditional morphometric approach, Romiti et al (2015) highlighted the presence of two morphological classes: large males (which invest significantly more in mandibles and head size) and minor males. Furthermore, a geometric morphometric approach revealed that smaller males show highly variable mandibles (usually less curve dorsoventrally, thickset, with barely outlined teeth and a head without prominent basal edges) whereas larger males exhibit less variable mandibles (slender and equipped with fully developed median teeth, and deep, divaricate apical forks, supported by wide head basal edges) (Romiti et al 2016).…”
Section: Morphologymentioning
confidence: 99%
“…BM was not measured for beetles sampled in CRO. Mandible length and elytron length were measured as described in Chiari et al (2014), Romiti et al (2015) and . Mandible length (ML) was measured as the linear distance from clypeus to the apex of the outer tooth of the fork and this can be considered a good proxy for the actual mandible size (Romiti et al 2016).…”
Section: Sampling Design and Study Areasmentioning
confidence: 99%
“…For the allometric analysis of male mandibles, the elytron length was used as an independent variable, mainly for three reasons: (i) its proven high correlation coefficient with mandible length (Romiti et al 2015); (ii) the comparability with previous morphometric studies which used linear distances for L. cervus (Harvey and Gange 2006, Hardersen et al 2011, Chiari et al 2014, Romiti et al 2015 and (iii) to avoid scale dependence issues in comparing traits with different units (e.g., mm vs g) which could affect the data despite the log transformation (Warton et al 2006). The pooled dataset was used to analyse the allometric relationship between the mandible length (LnML) and the elytron length (LnEL) of L. cervus males.…”
Section: Morphometry and Allometrymentioning
confidence: 99%
See 2 more Smart Citations